Question

Math

Posted 3 months ago

```
Find the differential of the function.
$z=e^{-2 x} \cos 2 \pi t$
```

Sign in to unlock the answer

Answer from Sia

Posted 3 months ago

Solution by Steps

step 1

We need to find the differential of the function $z = e^{-2x} \cos(2\pi t)$

step 2

To find the differential, we use the product rule for differentiation. The product rule states that if $u$ and $v$ are functions of $x$ and $t$, then $d(uv) = u \, dv + v \, du$. Here, $u = e^{-2x}$ and $v = \cos(2\pi t)$

step 3

First, we differentiate $u = e^{-2x}$ with respect to $x$:
$\frac{du}{dx} = \frac{d}{dx}(e^{-2x}) = -2e^{-2x}$

step 4

Next, we differentiate $v = \cos(2\pi t)$ with respect to $t$:
$\frac{dv}{dt} = \frac{d}{dt}(\cos(2\pi t)) = -2\pi \sin(2\pi t)$

step 5

Now, applying the product rule:
$dz = e^{-2x} \, d(\cos(2\pi t)) + \cos(2\pi t) \, d(e^{-2x})$

step 6

Substituting the derivatives we found:
$dz = e^{-2x} (-2\pi \sin(2\pi t) \, dt) + \cos(2\pi t) (-2e^{-2x} \, dx)$

step 7

Simplifying the expression:
$dz = -2\pi e^{-2x} \sin(2\pi t) \, dt - 2e^{-2x} \cos(2\pi t) \, dx$

Answer

The differential of the function $z = e^{-2x} \cos(2\pi t)$ is $dz = -2\pi e^{-2x} \sin(2\pi t) \, dt - 2e^{-2x} \cos(2\pi t) \, dx$.

Key Concept

Differentiation using the product rule

Explanation

The product rule is used to differentiate a product of two functions. In this case, we differentiated $e^{-2x}$ and $\cos(2\pi t)$ separately and then applied the product rule to find the differential of the given function.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Upgrade to Asksia Pro

Join a AskSia's Pro Plan, and get 24/7 AI tutoring for your reviews, assignments, quizzes and exam preps.

Unlimited chat query usages

Strong algorithms that better know you

Early access to new release features

Study Other Question